2010
DOI: 10.1038/nature09313
|View full text |Cite
|
Sign up to set email alerts
|

Glacier retreat in New Zealand during the Younger Dryas stadial

Abstract: Millennial-scale cold reversals in the high latitudes of both hemispheres interrupted the last transition from full glacial to interglacial climate conditions. The presence of the Younger Dryas stadial (approximately 12.9 to approximately 11.7 kyr ago) is established throughout much of the Northern Hemisphere, but the global timing, nature and extent of the event are not well established. Evidence in mid to low latitudes of the Southern Hemisphere, in particular, has remained perplexing. The debate has in part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
205
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(233 citation statements)
references
References 29 publications
28
205
0
Order By: Relevance
“…According to the current concept of north-south climate coupling, the resumption of southern warming at the end of the ACR was triggered by the onset of the YD stadial in the north (at 12.85 ka BP) (e.g. Denton et al, 2010;Kaplan et al, 2010). Our results, within dating uncertainties, remain consistent with this view but offer new detail.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…According to the current concept of north-south climate coupling, the resumption of southern warming at the end of the ACR was triggered by the onset of the YD stadial in the north (at 12.85 ka BP) (e.g. Denton et al, 2010;Kaplan et al, 2010). Our results, within dating uncertainties, remain consistent with this view but offer new detail.…”
Section: Resultssupporting
confidence: 81%
“…Previous studies confirm opposing climate trends on millennial timescales between the northern and southern mid to high-latitudes during this interval (e.g. Sowers and Bender, 1995;Blunier et al, 1998;Blunier and Brook, 2001;Shakun and Carlson, 2010;Kaplan et al, 2010). Antarctica first warmed during the glacial conditions of Greenland stadial 2 (GS-2), then cooled during the Antarctic Cold Reversal (ACR), as Greenland experienced the warmth of the Bølling-Allerød interstadial (B-A or GI-1a-e).…”
Section: Introductionmentioning
confidence: 71%
“…This good agreement between model and manual reconstruction of glacier ELAs echoes previous similar findings (e.g. Kaplan et al, 2010;Doughty et al, 2013), demonstrating the utility of simple ELA reconstructions for efficient extraction of palaeoclimate data from moraine records.…”
Section: Last Glacial Maximum Climate In New Zealandsupporting
confidence: 76%
“…This is important because some of the glaciers of New Zealand demonstrate asynchronous behaviour both regionally and also with northern hemisphere examples. For example, Schaefer et al (2009) found disparities between the timing of maximum Holocene ice extent around Mount Cook, New Zealand, and Kaplan et al (2010) describe glacier retreat in New Zealand during the Younger Dryas stadial. Furthermore, New Zealand presently only has one glacier, Brewster Glacier, in the World Glacier Monitoring Service (WGMS 2009;Zemp et al 2009).…”
Section: Glaciers Of the Southern Alps New Zealandmentioning
confidence: 99%